Symbol and tradition in the painting of Eudochia Robu - Natalia PROCOP (Dialogica: Revistă de Studii Culturale și Literatură)
Being an artist with deep visions, Eudochia Robu makes extensive use of symbols in her creation, in which no object appears by chance. Decoding them gives it depth. E. Robu is in the list of the most valuable artists in the republic. One of the symbols that has priority in the artist’s painting is that of the angel, which every time comes with a new social message. The angel appears engaged in various human activities: riding a bicycle, leswinging on the swing, sleeping: “Angel on a bicycle”, “Angel on a donkey”, “Angel and birds”, “Angel with white cherries”, “Sleeping angel IV” saddle, etc. Popular traditions and customs are one of the themes that Eudochia Robu often returns to in her paintings: the undressing of the bride, caloianul (a rainmaking and fertility rite in Romania), the winter holidays, etc. In this sense, we can mention the paintings: “Undressing the Bride”, “Winter landscape with carolers”, “Colind”, “Angel and carolers”, “Traditions”, “Calling the rain”, etc. Even works in the genre of landscape or painting of genre contain popular ornaments taken from the carpet, the popular shirt or traditional architecture: “Butuceni. Ornamental Landscape”, “Windy Day”, “Gate I”, “The Last Supper”, “Angel with Eagle”, “Sleeping Angel IV”, etc. Whatever symbol Eudochia Robu uses, the figurative becomes plastic expression in her paintings.